Types of pelvis in the Peruvian woman. Radiopelvimétrico study - Fernández Molinari, Luis (2015)
In a study of 320 radiopelvimetrías, between the years 1963-1968, we draw the following conclusions. 1 pelvis-The most commonly found were the Ginecoides, giving the total of 47.2%. Of these, the pure gynecoid contributed 24.4%, the gynecoid-android 9.7%, the gynecoid-platypelloid the 6.85% and finally gynecoid-Anthropoid 6.25%. 2. The pelvis platypelloid occupied in descending order, the second with a percentage of 40.95. Of these the Platipelo-gynecoid was 18.75%, the platypelloid-pure 17.2%, the Platipelo-android 3.7% and PIatipelo-Anthropoid 1.25%. 3.-type android pelvis were found in 6.25% of cases, occupying the third position in frequency. Of them he gave the Android-gynecoid 2.8%, with 2.5% pure Android, the Android-platypelloid 0.65% and 0.3% Android-Antopoide. 4 .- Finally, Anthropoids pelvis and represent 15.6% of our series, being pure Anthropoids the highest incidence with 4.35% and Anthropoid-gynecoid 1.25%.